2006
DOI: 10.1080/02640410600598281
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy effects in tennis: The impact of opponents' pre-match non-verbal behaviour on male tennis players

Abstract: In this study, we examined the impact of a male opponent's pre-match body language and clothing (general vs. sports-specific) on how his performances were judged by an observer. Forty male tennis players viewed videos of a male target tennis player warming up and then observed playing footage of the target. Each participant viewed the target player warming up displaying one of four combinations of body language and clothing (positive body language/tennis-specific clothing; positive body language/general sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
2
10
1
Order By: Relevance
“…Although they contradict the findings of Greenlees, Buscombe, et al (2005), who found that clothing did not affect opponent perception in a sporting context, they are supported by Buscombe et al (2006) and Greenlees, Bradley, et al (2005), whose results suggest clothing can affect perception in this context. The results of this study support existing research (Buscombe et al, 2006;Greenlees, Bradley, et al, 2005;Greenlees, Buscombe, et al, 2005;Greenlees et al, 2008) that shows increased opponent perception decreases outcome expectations. Similar-sized changes in opponent judgments and outcome expectations between studies suggest that the changes in perception caused by clothing and its effects on outcome expectations are comparable to those caused by body language.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Although they contradict the findings of Greenlees, Buscombe, et al (2005), who found that clothing did not affect opponent perception in a sporting context, they are supported by Buscombe et al (2006) and Greenlees, Bradley, et al (2005), whose results suggest clothing can affect perception in this context. The results of this study support existing research (Buscombe et al, 2006;Greenlees, Bradley, et al, 2005;Greenlees, Buscombe, et al, 2005;Greenlees et al, 2008) that shows increased opponent perception decreases outcome expectations. Similar-sized changes in opponent judgments and outcome expectations between studies suggest that the changes in perception caused by clothing and its effects on outcome expectations are comparable to those caused by body language.…”
Section: Discussioncontrasting
confidence: 84%
“…Despite research showing that opponent perception can affect performance, there is a paucity of literature examining what information affects perception. Some researchers (Buscombe, Greenlees, Holder, Thelwell, & Rimmer, 2006;Greenlees, Bradley, Holder, & Thelwell, 2005;Greenlees, Buscombe, Thelwell, Holder, & Rimmer 2005) have examined the impact of body language and clothing as forms of non-verbal behaviour. Greenlees, Bradley, et al (2005) measured the difference between participants' outcome expectations against an opponent and judgements of an opponent across four conditions, involving positive/negative body language and sport specific/general sports clothing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Buscombe, Greenlees, Holder, Thelwell and Rimmer (2006) revealed that the inferences tennis players made about their opponents' body language and clothing influenced their perceptions of the dispositional traits of their opponent and their perceived anticipated match outcome. Specifically, when opponents displayed confident body language, tennis players felt less likely to succeed against them and inferred that their opponents' confidence was due to their anticipation of victory.…”
Section: Observer's Inferencesmentioning
confidence: 98%
“…Greenlees, Dicks, Thelwell, & Holder, 2007). Other unconscious biases in sports include: heuristic reasoning (Miller, Rowe, Cronin, & Bampouras, 2012), prior exposure effects (Ste-Marie, Valiquette & Taylor, 2001), expectation effects (Buscombe, Greenlees, Holder, Thelwell, & Rimmer, 2006), or halo effects (Moormann, 1994). This knowledge may be used to develop strategies that protect judgments from being biased.…”
Section: Introductionmentioning
confidence: 99%